2016
DOI: 10.1002/ecs2.1606
|View full text |Cite
|
Sign up to set email alerts
|

The end of the mythical giant catfish

Abstract: Abstract. The European catfish Silurus glanis is the largest freshwater fish (excluding anadromous species) in Europe. Its measurements raise many concerns about its potential impact on recipient ecosystems and fish communities and also feed many rumors and fantasies. It is largely accepted that the largest individual ever caught was 5 m long and weighed 306 kg. This information has been reported in the scientific literature for at least a century and is now reported in numerous specialized Web sites. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Interestingly, comparisons of growth trajectories between our peripheral populations to those inhabiting core habitats suggest that the maximum size are similar regardless of area and this is also supported by capture data indicating that the maximum size throughout the distribution area is approximately 2–2.7 m 22 , 23 , 34 . Based on the slow growth in the peripheral habitat, this proposes that the major difference between populations is that individuals in peripheral habitats in Sweden become substantially older.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, comparisons of growth trajectories between our peripheral populations to those inhabiting core habitats suggest that the maximum size are similar regardless of area and this is also supported by capture data indicating that the maximum size throughout the distribution area is approximately 2–2.7 m 22 , 23 , 34 . Based on the slow growth in the peripheral habitat, this proposes that the major difference between populations is that individuals in peripheral habitats in Sweden become substantially older.…”
Section: Discussionsupporting
confidence: 74%
“…Catfish have previously been described as a solitary predator [48,91], possibly exhibiting territoriality [29,92,93], although the species can temporarily aggregate and form large clusters [94]. While we did observe similar clustering tendencies in the study lake during a post hoc video analysis (https://www.youtube.com/watch?v=9gdi6NLuHug) in the colder phases of the year, our clustering analyses suggested rather solitary behaviour at the intraspecific level overall.…”
Section: Discussionsupporting
confidence: 58%
“…It is generally accepted that the largest European catfish individual ever caught was 5 m long and weighing 306 kg. Boulêtreau and Santoul (2016) testified that at present, the accurate largest individual of the European catfish ( S. glanis ) was caught in the Rhone River (Southern France), measured (2.73 m) and weighed (130 kg). Although our study observed only one individual, it should be considered that it is objectively difficult to capture more large specimens in the investigated area (Cucherousset et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The European catfish ( Silurus glanis ) is the largest freshwater fish (excluding anadromous species) in European rivers, tolerant to brackish water and has an extensive geographical range (Boulêtreau & Santoul, 2016; Cucherousset et al, 2018). In western and southern Europe, it is considered as an invasive species with a negative effect on native fish fauna (Danek et al, 2014).…”
Section: Introductionmentioning
confidence: 99%